Correlation between Green Marketing Strategy and Organizationâ€™s Performance in Malaysia - Valliappan Raju, Assoc. Prof. Dr.; Md Rom Bin Tamjis, Prof Dr. (International Journal of Engineering and Technology, 2019)
This research sought to unearth how the green marketing strategy drives business success. Specific insights were gained from the context of Malaysia. Based on the current literature and the financial performance trend obtained, mixed results were obtained. Indeed, most of the studies concurred that for multinational corporations, there is an increasing trend in the green marketing strategy. These findings were confirmed by the data obtained for the case of Malaysia whereby the number of its firms around the world has increased steadily; implying that it is keen to exploit any potential markets that remain untapped.Â  It has been established that through the green marketing strategy, business success tends to be driven by the provision of lower prices to consumers, having utilised specialised labor in different countries in which companies establish operations. Also, the practice leads to increased global productivity due to the capacity to access international funds; eventually attracting the establishment of the state-of-the-art facilities.Â